Redox Homeostasis and Nrf2-Regulated Mechanisms Are Relevant to Male Infertility - Cinzia Signorini; Luciano Saso; Somayyeh Ghareghomi; Pelin Telkoparan-Akillilar; Giulia Collodel; Elena Moretti (MDPI AG, 2024)
Infertility represents a significant global health challenge, affecting more than 12% of couples worldwide, and most cases of infertility are caused by male factors. Several pathological pathways are implicated in male infertility. The main mechanisms involved are driven by the loss of reduction-oxidation (redox) homeostasis and the resulting oxidative damage as well as the chronic inflammatory process. Increased or severe oxidative stress leads to sperm plasma membrane and DNA oxidative damage, dysregulated RNA processing, and telomere destruction. The signaling pathways of these molecular events are also regulated by Nuclear factor-E2-related factor 2 (Nrf2). The causes of male infertility, the role of oxidative stress in male infertility and the Keap1-Nrf2 antioxidant pathway are reviewed. This review highlights the regulatory role of Nrf2 in the balance between oxidants and antioxidants as relevant mechanisms to male fertility. Nrf2 is involved in the regulation of spermatogenesis and sperm quality. Establishing a link between Nrf2 signaling pathways and the regulation of male fertility provides the basis for molecular modulation of inflammatory processes, reactive oxygen species generation, and the antioxidant molecular network, including the Nrf2-regulated antioxidant response, to improve male reproductive outcomes.